Collision‐induced dissociation studies of caffeine in positive electrospray ionisation mass spectrometry using six deuterated isotopomers and one N1‐ethylated homologue. (12th March 2013) - Bier, Dirk; Hartmann, Rudolf; Holschbach, Marcus
<x xml:space="preserve">Abstract</x> RATIONALE In order to deepen the understanding of electrospray ionisation collision‐induced dissociation (ESI‐CID) fragmentation reactions of xanthine derivatives for the identification of metabolites using low‐resolution liquid chromatography/mass spectrometry (LC/MS) analysis, basic experiments using caffeine (1, 3, 7‐trimethylxanthine) as model compound have been performed. METHODS Six deuterium isotopomers and one N1‐ethylated homologue of caffeine have been synthesized and their ESI fragmentation spectra have been obtained by using LC/MS in combination with either standard or perdeuterated eluent mixtures. RESULTS One result of these studies is the finding that the positive charges of the ESI‐CID caffeine fragments are caused by the addition of protons. Furthermore, the performed experiments allow the determination of all molecular formulae of each ESI‐CID caffeine fragment. CONCLUSIONS As basic CID reactions of caffeine have been elucidated in this work, the developed fragmentation scheme may serve as a valuable tool for the interpretation of ESI‐CID fragmentation spectra of more complex xanthine derivatives and their respective metabolites. Copyright © 2013 John Wiley & Sons, Ltd.